The effect of 60Co-gamma radio-sterilization on Boswellia carterii essential oil composition - P. Badr; S. Daneshamouz; A.A. Mohammadi; A.R. Akbarizadeh; S. Afsharypuor (Iranian Society of Pharmacognosy, 2016)
Background and objectives:Gamma-irradiation is used vastly for both decontamination and sterilization of natural products; but these high-energy rays can affect heat-sensitive essential oils. Methods: The oleo-gum-resin of Boswellia carterii (Burseraceae) was sterilized by γ-irradiation at dose 30 KGy. The essential oils obtained by hydrodistillation of non-irradiated Boswellia (NIB) and irradiated Boswellia (IB) were analyzed by GC/MS and the changes were compared. The structure of octyl acetate as the major component and marker of B. carterii was confirmed by MS/MS. Results: Twenty-five compounds comprising 99.55% of NIB oil and nineteen compounds comprising 98.61% of IB oil were identified. Major constituents which were common for both oils were octyl acetate (52.67 % in NIB, 76.51 % in IB), 1-octanol (6.37 % in NIB, 5.19 % in IB), duva-4, 8, 13-triene-1,3α diol (5.52 % in NIB, 3.94 % in IB), verticiol (13.63 % in NIB) and verticillane type diterpene (5.4 % in IB) they made up 78.19% and 91.04% of NIB and IB, respectively. Conclusion: Gamma irradiation was an efficient method for sterilization of Boswellia carterii oleo-gum resin, but it resulted in change in the essential oil composition particularly octyl acetate changed from 52.67% to 76.51%.